Snatch theft in Islamic law and Malaysian civil law : a comparative law - Nur Munira Roslan (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2016)
Snatch theft is one of the most serious and ugliest crimes rampant in Malaysia in recent times. It is of deep concern and a pressing threat to Malaysians due to the severity of its impact on the victims. The existing provisions governing the Penal Code seem ineffective and unreliable to address and curb this heartless crime. Therefore the adoption and implementation of Islamic law is called for. The primary purpose of this study is to examine and evaluate snatch theft from the Islamic law and Malaysian civil law points of view. This study evaluates Malaysian Civil law and Islamic law in tackling and treating this new type of theft crime through apparent relationship such as definition, elements, and punishments. The discussion starts with a description of snatch theft and its common features followed by the discourse among Muslim jurists regarding snatch theft and whether it is al-sariqah or al-ḥirābah, which is liable to ḥadd punishment. This study also examines snatch theft offences in Malaysian Civil law under Section 378 and Section 390 of the Penal Code. Using a qualitative method in collecting data through library research and descriptive and comparative analytical approaches, it is found in the study that there are some undeniable similarities and differences between these two legal systems. On the basis of the results of this research it can be concluded that notwithstanding safety and prevention measures taken to curb snatch theft cases, the comparative analysis between these two legal systems highlights the need for proper legislation on snatch theft crime. It is hoped that this study offers all rationales and useful recommendations to improve Malaysian Civil law on snatch theft offences as well as an orientation for future comparative law study.